Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20174304
|View full text |Cite
|
Sign up to set email alerts
|

DNA- and DNA-Protein-Crosslink Repair in Plants

Abstract: DNA-crosslinks are one of the most severe types of DNA lesions. Crosslinks (CLs) can be subdivided into DNA-intrastrand CLs, DNA-interstrand CLs (ICLs) and DNA-protein crosslinks (DPCs), and arise by various exogenous and endogenous sources. If left unrepaired before the cell enters S-phase, ICLs and DPCs pose a major threat to genomic integrity by blocking replication. In order to prevent the collapse of replication forks and impairment of cell division, complex repair pathways have emerged. In mammals, ICLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 163 publications
(217 reference statements)
0
12
0
Order By: Relevance
“…For the CPT + NSC combination, both PCD and necrosis events are present at similar levels while the high levels of DNA damage indicate the most genotoxic effect. Previous literature reports that CPT results in the accumulation of DPCs ( Enderle et al, 2019b ) and DSBs ( Ferrara and Kmiec, 2004 ; Berniak et al, 2013 ), lesions know to be associated with necrotic events in plant cells ( Rowan et al, 2010 ; Song and Bent, 2014 ). On the other hand, low concentrations of NSC120686 resulted in enhanced levels of PCD in M. truncatula calli ( Macovei et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the CPT + NSC combination, both PCD and necrosis events are present at similar levels while the high levels of DNA damage indicate the most genotoxic effect. Previous literature reports that CPT results in the accumulation of DPCs ( Enderle et al, 2019b ) and DSBs ( Ferrara and Kmiec, 2004 ; Berniak et al, 2013 ), lesions know to be associated with necrotic events in plant cells ( Rowan et al, 2010 ; Song and Bent, 2014 ). On the other hand, low concentrations of NSC120686 resulted in enhanced levels of PCD in M. truncatula calli ( Macovei et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overexpression of TDP2α gene in M. truncatula was correlated with a decrease in the accumulation of DSBs, increased cell proliferation, and enhanced resistance to stress ( Confalonieri et al, 2014 ; Faè et al, 2014 ; Araújo et al, 2016 ). Genes involved in DNA repair alternative to TDP1 ( Pommier et al, 2014 ) include the MNR complex, composed of MRE11 , NBS1 , and Rad50 , known to be involved in the detection of DBSs and HR ( Manova and Gruszka, 2015 ) as well as PARP1 , MUS81 , and ERCC1 involved in BER and DPC repair ( Enderle et al, 2019b ; Roldán-Arjona et al, 2019 ). Since DDR includes a response from both DNA repair and cell cycle regulation, several cyclins ( Cdka1 , Cycb1 , Cycd2 , and Cycd3 ) were investigated alongside the master-regulators TOR and SOG1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the important role that DNA repair has during plant development, for instance as shown by the presence of specific DNA stress checkpoint controls [76], it is well ascertained that different types of stress conditions induce DNA damage and DNA repair pathways are activated to counteract it [77,78]. In this context, the function of TDP1 was associated with the base excision repair (BER) pathway [18,79], as well as with the repair of DNA-protein crosslinks [16,17]. In this work, concerning the response of the TDP1 genes to abiotic stress conditions, two distinct patterns can be discussed: (1) a similar behavior of the genes in response to osmotic and temperature-related stresses (e.g., salt, cold); and (2) opposing behavioral patterns in response to desiccation and anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis tdp1 mutants presented a different developmental phenotype characterized by dwarfism caused by a decreased number of cells, while the use of vanadate inhibited the AtTDP1 enzymatic activity and further retarded the growth of the mutant [15]. More recently, it has been demonstrated that AtTDP1 participates in the repair of DNA-protein crosslinks (DPC), as a backup pathway independent of MUS81 endonuclease and WSS1 protease [16,17]. Interestingly, in 2010, a small subfamily of TDP1 genes was identified in the model legume Medicago truncatula [5].…”
Section: Introductionmentioning
confidence: 99%